Muscle-Specific Kinase Myasthenia Gravis - Borges, Lucia S.; Richman, David P. (Frontiers in Immunology, 2020)
Thirty to fifty percent of patients with seronegative myasthenia gravis have antibodies to muscle specific kinase (MuSK) and are referred to referred to as having MuSK-myasthenia. MuSK, a 100kD single-pass post-synaptic transmembrane receptor tyrosine kinase, is crucial to the development and maintenance of the neuromuscular junction. The molecule comprises an N-terminal extracellular domain, which functions as a receptor for the nerve terminal secreted signaling protein agrin, followed by a short transmembrane domain and then a C-terminal cytoplasmic kinase signaling domain. The extracellular domain of MuSK consists of three immunoglobulin (Ig)-like domains followed by a cysteine-rich (frizzled-like) C6 box region. The antibodies in MuSK-myasthenia bind primarily to the first 2 Ig-like domains and are predominantly of the IgG4 subclass. Anti-MuSK myasthenia differs from seropositive myasthenia gravis, in which the autoantibodies are directed at the postsynaptic neurotransmitter receptor, nicotinic acetylcholine receptor (AChR), in exhibiting more focal muscle involvement, frequently including neck, shoulder, facial and bulbar-innervated muscles as well as wasting of the involved muscles. MuSK-myasthenia is highly associated with the HLA DR14-DQ5 allele and occurs predominantly in females with onset in the fourth decade of life. Many of the standard treatments of AChR-myasthenia have been found to have limited effectiveness in MuSK-MG: Thymectomy has not been shown to be effective, consistent with the absence of histologic changes in the thymus in this disease. Also, cholinesterase inhibitors have not been effective, and, in many patients, they have appeared to worsen myasthenic symptoms. Therefore, current treatment involves immunosuppression, primarily by corticosteroids. In addition, patients respond especially well to B cell depletion agents, e.g., rituximab, with long-term remissions. Future treatments will likely derive from the ongoing analysis of the pathogenic mechanisms underlying this disease, which come from histologic and physiologic studies of the neuromuscular junction in patients with the disease as well as information derived from the development and study of animal models of the disease produced by either passive transfer of patient serum or active immunization with MuSK protein.